1993
DOI: 10.1111/j.1365-2621.1993.tb04248.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition of Goat Organ and Muscle Meat of Alpine and Nubian Breeds

Abstract: Fatty acid compositions of liver, heart, kidney, Longissimus dorsi (LD) and Biceps femoris (BF) of two goat breeds were evaluated using capillary gas chromatography (GC). Laurie (C12:O) acid was absent from the liver and kidney. All organ samples had significantly (P < 0.01) greater polyunsaturated fatty acids (PUFA) than the LD and BF muscles. The organs also contained significantly (P c 0.01) higher saturated fatty acids (SFA) than the skeletal muscles, whereas the opposite trend occurred for the Cl&l conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
5
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 16 publications
(14 reference statements)
6
23
5
2
Order By: Relevance
“…Goats deposit more internal fat, mainly in abdominal cavity and viscera, and less subcutaneous and intramuscular fat, compared with sheep or even cows and pigs (Banskalieva et al, 2000;Madruga, 1999). Park and Washington (1993) and Park et al (1991) quantified total fat, fatty acids and cholesterol in certain organs and muscles of Alpine and Nubian goats, and confirmed these findings. As in Latin-American countries and other undeveloped countries the consumption of goat viscera and their formulated products is a reality and the need of information on their fat composition is beyond dispute.…”
Section: Introductionsupporting
confidence: 59%
“…Goats deposit more internal fat, mainly in abdominal cavity and viscera, and less subcutaneous and intramuscular fat, compared with sheep or even cows and pigs (Banskalieva et al, 2000;Madruga, 1999). Park and Washington (1993) and Park et al (1991) quantified total fat, fatty acids and cholesterol in certain organs and muscles of Alpine and Nubian goats, and confirmed these findings. As in Latin-American countries and other undeveloped countries the consumption of goat viscera and their formulated products is a reality and the need of information on their fat composition is beyond dispute.…”
Section: Introductionsupporting
confidence: 59%
“…In the present study, the proportions of desirable fatty acids (DFA) ranged within 60.5-68.8%. Other authors, for the same muscles in other goat breeds, reported 61.3-79.8% of DFA (Matsuoka, Furokawa, & Takahashi, 1997;Park & Washington, 1993;Potchoiba, Lu, Pinkerton, & Sahlu, 1990). Recently reported DFA in the pelvic limb fat of suckling kids were 49.4% and 53.1% for Girgentana kids (Todaro et al, 2002) slaughtered at two different ages (25 and 35 days, respectively) and 46.3% for Nebrodi kids slaughtered at 47 days of age Table 7 Analysis of variance and least-squares means (± standard error) of longissimus thoracis et lumborum (LTL) muscle sarcomere length (lm) of male and female kids carcasses of Serrana (S), Bravia (B) and Serrana · Bravia (S·B) crossbred genotypes (Todaro et al, 2004).…”
Section: Fatty Acid Compositionmentioning
confidence: 54%
“…Outros ruminantes, como os bovinos e caprinos apresentam praticamente o mesmo perfil dos ovinos. Os ácidos graxos oléico (C18:1), palmítico (C:16:0) e esteárico (C18:0) (Park & Washington 1993;Enser et al, 1996).…”
Section: Resultsunclassified